Assessment of the Opening Minds Scale for use with nursing students. Issue 4 (6th June 2019) - Happell, Brenda; Platania‐Phung, Chris; Scholz, Brett; Bocking, Julia; Horgan, Aine; Manning, Fionnuala; Doody, Rory; Hals, Elisabeth; Granerud, Arild; Jan van der Vaart, Kornelis; Allon, Jerry; Lahti, Mari; et al.
Abstract: Purpose: Evaluate the validity of the Opening Minds Scale (OMS) for nursing students via Rasch models and confirmatory factor analysis (CFA). Design and methods: Undergraduate nursing student responses to OMS (n = 423). Validity was evaluated via CFA and Rasch analysis. Findings: CFA results were strongest for a three‐factor 13‐item version of OMS. Rasch modeling supported sound properties for two of three scales. Internal reliabilities ranged between 0.6 and 0.7. Practice implications: OMS has potential as a valid measure for stigma research and antistigma program evaluation. Rasch analysis suggest it is inappropriate to use a total OMS score for nursing student populations.